IMPLEMENTATION OF EUNETHTA CORE MODEL® IN LOMBARDIA: THE VTS FRAMEWORK. (22nd January 2014) - Radaelli, Giovanni; Lettieri, Emanuele; Masella, Cristina; Merlino, Luca; Strada, Alberto; Tringali, Michele
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: This study describes the health technology assessment (HTA) framework introduced by Regione Lombardia to regulate the introduction of new technologies. The study outlines the process and dimensions adopted to prioritize, assess and appraise the requests of new technologies. Methods: The HTA framework incorporates and adapts elements from the EUnetHTA Core Model and the EVIDEM framework. It includes dimensions, topics, and issues provided by EUnetHTA Core Model to collect data and process the assessment. Decision making is instead supported by the criteria and Multi-Criteria Decision Analysis technique from the EVIDEM consortium. Results: The HTA framework moves along three process stages: (i) prioritization of requests, (ii) assessment of prioritized technology, (iii) appraisal of technology in support of decision making. Requests received by Regione Lombardia are first prioritized according to their relevance along eight dimensions (e.g., costs, efficiency and efficacy, organizational impact, safety). Evidence about the impacts of the prioritized technologies is then collected following the issues and topics provided by EUnetHTA Core Model. Finally, the Multi-Criteria Decision Analysis technique is used to appraise the novel technology and support Regione Lombardia decision making. Conclusions: The VTS (Valutazione delle Tecnologie Sanitarie) framework has been successfully implemented at the end of 2011. From its inception, twenty-six technologies have been processed.